Age and Prostatic Volume: The Prognosis for Benign Prostatic Hyperplasia - Dr. Afsheen Khan; Dr. Saif Ullah Shaikh; Dr. Rabiya Ali Ali; Dr. Syed Bushra Ahmed (ziauddin University, 2024)
Background: Old age is more susceptible to prostatic sicknesses. Benign prostatic hyperplasia (BPH) is related to repeated urinary tract infections, which influences personal satisfaction. The values of prostatic volume and obesity are viewed as significant factors for the advancement of prostate organ hypertrophy. The study aimed to investigate the effect of age on benign prostatic hyperplasia patients in a tertiary care hospital in Karachi. Methods: A cross-sectional study was conducted in an emergency clinic of Dr. Ruth Pfau and Dow College of health sciences on 60 enrolled patients (50-80 years). All selected patients had BPH and were assessed by a Global prostate side effect score >7. Patients with BPH were divided into two groups obese and non-obese. Transrectal ultrasound was performed to analyze the length, width, diameter and volume of the prostate. The outcomes were then examined to observe the progressions in the morphological construction of the prostate and its relationship with the advancement of age. Results: The mean prostate volume (PV) was higher in the obese group measuring 36.13±3.673ml while in the non-obese group, it was 31.21±6.771 ml, the difference was statistically significant (p=0.001). In the 60-70 years, age group, we obtained the highest count of obese participants with PV ≥ 30ml. In 71-80 years, age groups, again the maximum number of participants had ≥ 30ml PV and were obese. Conclusion:  In the study, patients' obesity had a significant effect on the prostate volume (p<0.001). Thus, benign prostatic hypertrophy was seen in the higher age group (60-70 years). Keywords: Old Age, BPH, Prostatic Volume, Satisfaction.